2014
DOI: 10.1590/s1516-14392014005000091
|View full text |Cite
|
Sign up to set email alerts
|

Compressive strength, microstructure and hydration products of hybrid alkaline cements

Abstract: Ordinary Portland cement (OPC) is the dominant binder in the construction industry with a global production that currently reaches a total of 3 Gt per year. As a consequence, the cement industry's contribution to the total worldwide CO 2 emissions is of about 7% of the total emissions. Publications on the field of alkali-activated binders (also termed geopolymers), state that this new material is, potentially, likely to become an alternative to Portland cement. However, recent LCA studies show that the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 29 publications
3
22
0
2
Order By: Relevance
“…Projection of gel chemistry showed that a lower content of calcium in the proportion mix could produce a N-A-S-H gel. Similar findings were observed in [59], wherein the formation of N-A-S-H gel demonstrates that some sodium replaces calcium in the C-S-H matrix. On the other hand, a higher content of calcium could produce a chain silicate of C(-A)-S-H gel.…”
Section: Samplesupporting
confidence: 81%
“…Projection of gel chemistry showed that a lower content of calcium in the proportion mix could produce a N-A-S-H gel. Similar findings were observed in [59], wherein the formation of N-A-S-H gel demonstrates that some sodium replaces calcium in the C-S-H matrix. On the other hand, a higher content of calcium could produce a chain silicate of C(-A)-S-H gel.…”
Section: Samplesupporting
confidence: 81%
“…It is also possible to observe a more compact hydration products matrix in the presence of more activator (Figure 5), which could be an indicative of the improvement of the properties with more activator, at least with the quantities that are used in this work and in this Is worth to notice that in all the systems, can clearly be observed bands at the region around 1490-1440 cm −1 related by bonds type O-C-O with vibrations of asymmetrical tension of CO 3 2− can be clearly observed [38], which could be related with the carbonation of the alkali activation solution, reported in other studies [39]. Nevertheless, in some cases could be attributed to the formation of sodium carbonate, which has been observed in similar samples [40,41]. There is an agreement in the literature that the structural evolution of most of the alkali activation is concentrated in the main asymmetric band at around 1200-900 cm −1 that originates from bonds T-O-T, where T is Si or Al.…”
Section: Scanning Electron Microscopysupporting
confidence: 69%
“…Other authors [36] even reported a compressive strength decrease for one-part geopolymers based on calcined red mud and sodium hydroxide blends just after the first week of curing. Abdollahnejad et al [37,38] investigated one-part geopolymers having obtained relevant compressive strength by using fly ash and minor amounts of OPC. Cristelo et al [23] compared the carbon dioxide emissions of 3880 m 3 of Portland cement and geopolymer-based mixtures for jet-mix columns and mentioned that the AACB solution is responsible for just 77% of the Portland cement-based emissions.…”
Section: Carbon Dioxide Emissions Of Aacbmentioning
confidence: 99%